BEYOND THE CLASSROOM : HOW ENTREPRENEURIAL EDUCATION AND CREATIVITY DRIVE STUDENT ENTREPRENEURIAL INTEREST THROUGH MOTIVATION AT MULAWARMAN UNIVERSITYrsity - Musmadhina; Poppy Alvianolita Sanistasya; Lailatul Hijrah; Rosyid Nurrohman (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
This study aims to examine and analyze the relationship between entrepreneurship education and creativity on students' entrepretneurial interest, with entrepreneurial motivation as a mediating variable. The background of this research is grounded in the importance of shaping young entrepreneurs’ character in facing employment challenges and increasingly competitive economic growth. The study employed a quantitative approach using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS), processed through SmartPLS software. The sampling technique used was accidental sampling, and data were collected through an online questionnaire distributed to 100 active students of Mulawarman University who had completed an entrepreneurship course. The results show that creativity has a significant and positive influence on both entrepreneurial motivation and entrepreneurial interest, and entrepreneurial motivation is proven to be a strong determinant of students’ interest in engaging in entrepreneurial activities. On the other hand, entrepreneurship education does not have a significant effect on either entrepreneurial motivation or interest. These findings imply that fostering entrepreneurial interest among students is more influenced by internal drive and individual creative capacity rather than formal delivery of entrepreneurship content. Therefore, a more practical, inspirational, and experience-based approach to entrepreneurship education is needed to effectively stimulate students’ motivation and creativity.